Literature Review: Determinan Penerimaan Vaksinasi COVID-19 pada Ibu Hamil - Ayanasva, Khafina; Wiranti, Bella; Puspita, Anggraeny Dian; Azzahra, Amaliyah; Maajid, Sekar Khofidfah; Rejeki, Dwi Sarwani Sri (Dian Nuswantoro Semarang, 2023)
The COVID-19 virus that attacks the respiratory system, ranging from mild, and moderate, to death can affect anyone, including pregnant women. Vaccination has proven effective in dealing with the spread of COVID-19 cases. However, the majority of pregnant women are reluctant to receive vaccinations because of their fear. The research aims to determine the determinants of receiving COVID-19 vaccination in pregnant women to reduce their anxiety and be encouraged to be vaccinated. This study uses a literature review method from journals published between 2017-2022 in Science Direct, PubMed, and Google Scholar with the keywords acceptance, vaccine COVID-19, and pregnant. The total results from the literature study obtained 13 articles that met the inclusion criteria. The result of this literature review is that the low acceptance of COVID-19 vaccination is seen in young pregnant women, but in China itself, younger pregnant women receive the vaccine higher; exposure to negative information about vaccines; non-white race; religious beliefs in Ethiopia; lack of knowledge about the COVID-19 vaccine and evidence of vaccine safety in pregnant women, causing fear of the vaccine's effect on the fetus; perceived low susceptibility to COVID-19; low-income mothers; residence in rural areas; and a less motivating environment for COVID-19 vaccination.